Hubungan Kualitas Pelayanan Kesehatan dengan Kepuasan Pasien BPJS di Wilayah Kerja Puskesmas Mokoau Tahun 2026 - Sendi Selfiana Kaliele; Sartiah Yusran; Rahman Rahman (STIKES Columbia Asia Medan, 2026)
Patient satisfaction with healthcare services remains a major concern in the delivery of healthcare. The behavior of healthcare workers, including friendliness, politeness, and communication skills, plays an important role in improving patient satisfaction. Preliminary data indicated that the number of BPJS patient visits at BLUD UPTD Puskesmas Mokoau had decreased annually, while the results of the patient satisfaction survey were still not optimal because several health programs had not achieved the targeted service standards. This study aimed to analyze the relationship between the quality of healthcare services and BPJS patient satisfaction in the working area of Puskesmas Mokoau in 2025. This research applied a quantitative method with a descriptive-analytic approach using a cross-sectional study design. The study involved 306 respondents selected through a random sampling technique, ensuring that each member of the population had an equal opportunity to be chosen as a research sample. Data were collected using questionnaires and analyzed through the Chi-Square test. The findings revealed significant relationships between facilities, procedures, interaction, and communication with BPJS patient satisfaction, with each variable obtaining a P-value of 0.000 (<0.05). Therefore, the quality of healthcare services is closely associated with the level of patient satisfaction, indicating that healthcare workers need to improve service quality effectively and professionally.